O beijo no asfalto: melodrama na adaptação cinematográfica da obra de Nelson Rodrigues - Pinheiro, Pablo Marquinho Pessoa (2017)
The melodrama is popularly known as a genre that takes the viewers to tears, composed by great sentimentalism and exaggerated actors. Despite this popular idea has a real root, the melodrama characterizes itself mainly by the complex relationship with the public. This relationship of communication with viewers was determinant and strategic for the development of melodrama, as well as your upgrade and migration to other narrative forms. The first part of this research proposes a historic rescue of melodrama while genre, from its emergence in the theater during the 18TH century until their update by the cinema. The second part analyzes the relationship between melodrama, film and reception, from the studies on the cultural performances, it being understood that the viewer participates actively in the process of reception during a film session. Recognizing that updating the melodrama has kept a poetic communication full of emotion and with a strong educative and regulatory function. In the third part, one examines the film O Beijo no Asfalto, by Bruno Barreto, adapted from the eponymous dramaturgical text O Beijo no Asfalto, by Nelson Rodrigues. Searching elements that characterizes the melodramatic imagination, as well as, to point characteristics from melodrama reverberated in this film.